Correlation between anti-Mullerian hormone, luteinizing hormone, follicle-stimulating hormone, thyroid-stimulating hormone, estradiol, and vitamin D: a retrospective study in women with secondary infertility - Moradi Ghadi, Zahra; Saffarieh, Elham; Ezzedin, Maryam; Yousefi, Behpoor; Azargoon, Azam; Ziari , Abbas; Hemmatian , Najme; Azad, Nahid (Novelty in Biomedicine, 2025)
Background: This study aims to evaluate the correlation between anti-Müllerian hormone, luteinizing hormone, follicle-stimulating hormone, thyroid-stimulating hormone, Estradiol, and vitamin D in women experiencing secondary infertility. Materials and Methods: In this retrospective study, we enrolled 97 women with secondary infertility who underwent treatment between 2012 and 2022. Information regarding each couple, including names (confidential and coded), ages, causes of infertility, number of children and abortions, and duration of infertility were collected. Laboratory test results were gathered, which included gonadotropin and estradiol hormone levels measured on the second to third day of menstruation, as well as anti-Müllerian hormone, thyroid-stimulating hormone, and vitamin D levels. The data were analyzed using SPSS software (version 26). Results: The mean ages of females and males were 33/5±4/4 and 36/5±5/6 years, respectively. There was no significant correlation between vitamin D and estradiol and other hormone levels. In addition, there was a significant positive correlation between the follicle-stimulating and luteinizing hormones (P = .021). The luteinizing hormone also showed a significant negative correlation with the thyroid-stimulating hormone (P=.019). Conversely, anti-Müllerian hormone correlated negatively with follicle-stimulating hormone (P < 0.01). The age of females had a negative significant correlation with anti-Müllerian hormone (P=0.002). Conclusion: According to our study, as women age, their anti-Müllerian hormones decrease, and their follicle-stimulating hormone levels increase. In addition, the study found a correlation between luteinizing hormone and thyroid-stimulating hormone, indicating a potential interplay between thyroid function and reproductive hormones. The findings emphasize the complex relationships between age, hormonal levels, and secondary infertility.